Graphene oxide membranes with a confined mass transfer effect for Li+/Mg2+ separation: a molecular dynamics study. Issue 42 (21st October 2022) - Wu, Jinman; Li, Nan; Liu, Shengkai; Shi, Wenxiong; Min, Chunying; Zhu, Bo; Shao, Ruiqi; Pei, Xiaoyuan; Cai, Zhijiang; Xu, Zhiwei
Abstract : Molecular dynamics simulations were used to investigate the influence of the confined mass transfer effect on the separation of Mg 2+ and Li + from graphene oxide membranes, both in terms of layer spacing and degree of oxidation. Abstract : Membrane separation technology represented by graphene oxide (GO) membranes has been widely used in lithium extraction from salt lakes. It is extraordinary to study the extraction of Li + by GO membranes from the perspective of the confined mass transfer effect. This study establishes a GO channel model with the confined mass transfer effect to closely fit the actual mass transfer process. Meanwhile, this study investigates the dynamic fluid characteristics in the separation of Li + /Mg 2+ by GO membranes using molecular dynamics simulations. The results showed that the Li + /Mg 2+ separation ratio is maximum at 1.0 nm layer spacing and 10% oxidation degree of the GO membrane. Water molecules form a bilayer within the channel at the appropriate interlayer channel (1 nm) and oxidation level (10%), which accelerates the ion transport rate. Furthermore, the GO oxidation group has the weakest hydrogen bonding effect on water which promotes the passage of water. Finally, the maximum separation ratio is reached due to the fact that the binding force of Li + to water molecules in the channel is lower than that of Mg 2+ . The results of this study will provide theoretical consideration for the design of high-performance Li + /Mg 2+ separation membranes.